2009
DOI: 10.1007/s00383-009-2371-5
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome of asymptomatic patients with congenital cystic adenomatoid malformation

Abstract: This study suggests patients who present with asymptomatic CCAM will subsequently become symptomatic. Early surgical referral and intervention may be beneficial to avoid the development of complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(65 citation statements)
references
References 33 publications
2
61
0
2
Order By: Relevance
“…Congenital cystic adenomatoid malformations are classified into 5 types-0 to 4-using the Stocker classification [3][4][5]. Type 1 is associated with the best overall prognosis and may remain undetected until later in life, as in the present case.…”
Section: Discussionmentioning
confidence: 86%
“…Congenital cystic adenomatoid malformations are classified into 5 types-0 to 4-using the Stocker classification [3][4][5]. Type 1 is associated with the best overall prognosis and may remain undetected until later in life, as in the present case.…”
Section: Discussionmentioning
confidence: 86%
“…Lobectomy is considered by some to be the procedure of choice for removal of CLMs [12][13][14][15] because complete resection of the diseased lobe leaves no possibility for residual disease [16,17] and the resultant risk of recurrent infection or malignant transformation [18][19][20][21][22]. In addition, some authors have speculated that the rate of postoperative air leak is less with lobectomy [3].…”
Section: Discussionmentioning
confidence: 99%
“…Sauvat et al, reported that 3 out of 29 patients with CPAM experience symptoms during the first weeks of life [17]. As many as 86% (18 out of 21) of patients, who were asymptomatic at birth, had become symptomatic by 13 years of age (median age of 2 years) [22]. In patients with CPAM, pneumonia with or without infected CPAM was reported in 43%, respiratory distress in 14%, and spontaneous pneumothorax in 14% [22].…”
Section: Congenital Pulmonary Airway Malformation (Cpam)mentioning
confidence: 99%